Monitoring of concrete hydration by electrical measurement methods - Kusák, Ivo; Luňák, Miroslav; Chobola, Zdeněk (Elsevier, 2016)
Analysis of impedance spectra of inhomogeneous materials is a part of the impedance spectroscopy which is still waiting for its development. Materials having higher electric resistance values (over 500 kohm) can be considered – under certain simplifying assumptions – as dielectrics. A theory of dielectric polarization was formulated by Debye for homogeneous materials.

Analysis of impedance spectra of inhomogeneous materials is a part of the impedance spectroscopy which is still waiting for its development. Materials having higher electric resistance values (over 500 kohm) can be considered – under certain simplifying assumptions – as dielectrics. A theory of dielectric polarization was formulated by Debye for homogeneous materials.
Monitoring of concrete hydration by electrical measurement methods
Keywords: Impedance spectroscopy; dielectric losses; loss factor; conductivity losses; polarization losses; hydratation; concrete; Impedance spectroscopy; dielectric losses; loss factor; conductivity losses; polarization losses; hydratation; concrete